Efektivitas Akuntansi Digital Ditinjau Dari Digital Literacy, Relative Advantage, Competitive Preasure, dan Compability - Thalib, Maryati Kadir; Suleman, Fitrianti (Universitas Gorontalo, 2024)
This research aims to measure the extent of the influence of digital literacy, relative advantage, competitive pressure, and compatibility on the effectiveness of digital accounting utilization for micro, small, and medium enterprises (MSMEs) in Telaga Biru District using the Technology Organization Environment (TOE) method. The data analysis method used in this research is regression analysis with the assistance of SPSS version 24 software. The results of this research indicate that, partially, digital literacy, relative advantage, competitive pressure, and compatibility have a positive and significant influence on the effectiveness of digital accounting utilization for micro, small, and medium enterprises (MSMEs) players in Telaga Biru District. Simultaneously, digital literacy, relative advantage, competitive pressure, and compatibility have an influence on the effectiveness of digital accounting utilization for micro, small, and medium enterprises (MSMEs) players in Telaga Biru District.